(untitled) (Journal of actual problems of jurisprudence, 2023)
The exterritorial application of U.S. laws is also known as a «long arm jurisdiction» worldwide. «Long arm jurisdiction» is a concept based on the theory of the minimum contact of the United States, is an act of the United States’ rule of law against judicial sovereignty of other countries to safeguard its «world empire» status. The understanding of long arm jurisdiction can not be limited to the superficial dogmatic interoperation but should be placed in the perspective of global politics. This paper deconstructs the long arm jurisdiction from its evolution, mode and essence reveals the violent factors inside the legal basis of the long arm jurisdiction and explores the possibility of its salvation. The article raises the problem of the extraterritorial application of American prohibitions and restrictions to non - residents of the United States. Based on the meager judicial practice of the American federal courts of recent years, the issue of the extraterritorial application of the US sanctions legislation is being considered. In the investigated what are the answers given, why it is difficult for a foreign defendant to use in his defense the argument about the illegality of extraterritorially applied US legislation. Answers are given on how not to lose your investments due to the formal requirements of the American sanction’s legislation or due to the bad faith of the American partner. Keywords: long arm jurisdiction, law’s empires, deconstruction, salvation, legal, power, state.